Osnovi rozvitku admìnìstrativnogo prava u Lʹvìvsʹkomu unìversitetì - Kahnič, Volodimir (Wydawnictwo Uniwersytetu Wrocławskiego, 2022)
The article is devoted to the development of administrative law at the Faculty of Law of Lviv University since 1784. The formation and development of administrative law at Lviv University had certain specific features, and it was necessary to involve specialists from different universities to exchange experiences and proposals to current legislation, which was not common practice in the 17th and 18th centuries. The contribution of the employees of administrative law of Lviv University to the science of administrative law is demonstrated in the article. It is shown how administrative law was introduced at Lviv University and who practised it. The department’s activity at different stages of formation of the law faculty of Lviv University is also examined in this publication. The importance of many heads of the Department of Administrative Law and their contribution to the development and activities of the department are analyzed. Reforming administrative law in Ukraine today is extremely important for the current as well as the next generation. The use of historical experience, based on the example of the Faculty of Law of Lviv University, namely, the formation and operation of the Department of Administrative Law, has brought invaluable insights for reforming the science of administrative law. The reform of the science of administrative law today will help us better understand the value of the origins of scientific concepts that were formed and are still being formed under the influence of different historical periods, which were initiated by scholars of Lviv University. Such awareness and vision of the reform process and its scientific concepts can expand the scientific worldview of Ukrainian lawyers and ensure the improvement of practical results of legislative and law enforcement activities in improving the role and importance of the science of administrative law. Administrative law at the Faculty of Law of Lviv University has been shaped by a circle of like-minded people who taught the next generation, passing on their skills and knowledge. But thanks to the science of administrative law the foundations of the Faculty of Law of Lviv University were formed, which helped in the further development of administrative law in Ukraine.
Keywords: Lviv University; Faculty of Law; Department of Administrative Law; administrative law; Lʹvìvsʹkij unìversitet; ûridičnij fakulʹtet; kafedra admìnìstrativnogo prava; nauka admìnìstrativnogo prava